Perpetuation of inflammation associated with experimental arthritis: the role of macrophage activation by neutrophilic myeloperoxidase. Issue 6 (1998) - Gelderman, Monique P.; Stuart, Rodney; Vigerust, David; Fuhrmann, Steven; Lefkowitz, Doris L.; Allen, Robert C.; Lefkowitz, Stanley S.; Graham, Susan
Abstract : Rheumatoid arthritis (RA) is characterized by an abnormal cellular and cytokine infiltration of inflamed joints. This study addresses a previously unrecognized interaction between neutrophilic-myeloperoxidase (MPO) and macrophages (MΦ) which could explain the perpetuation of inflammation associated with RA. A monoarticular arthritis was induced in female Lewis rats by injection of streptococcal cell wall extracts (PG-APS). After swelling and erythema subsided, joints were re-injected with one of the following: porcine MPO or partially inactivated MPO (iMPO). Injection with either MPO or iMPO induced a 'flare' of experimental RA. Blocking the MΦ-mannose receptor by mannans, ablated exacerbation of disease. These results indicate that MPO or iMPO can play a pivotal role in the perpetuation but not initiation of this RA model.